Drag me to hell - Tapert, Rob; Curtis, Grant; Raimi, Sam; Raimi, Ivan; Universal Pictures; Ghost House Pictures ([California] : Universal Studios, 2009)
Christine Brown is an ambitious L.A. loan officer. She is on a desperate quest to break an evil curse. Professor Clay Dalton is her charming boyfriend. Life is good until the mysterious Mrs. Ganush arrives at the bank to beg for an extension on her home loan. Christine denies the extension to impress her boss and get a leg-up on a promotion, shaming Mrs. Ganush and dispossessing her of her home. She finds herself the recipient of a supernatural curse, which turns her life into a living hell
Title from container
Director of photography, Peter Deming ; editor, Bob Murawski ; music, Christopher Young ; special makeup effects, Gregory Nicotero, Howard Berger
Cast : Alison Lohman, Justin Long, Ruth Livier, Lorna Raver, Dileep Rao
DVD format
With optional English, Chinese or Malay subtitles
Keywords: Loan officers -- California -- Los Angeles -- Drama; Blessing and cursing -- California -- Los Angeles -- Drama; Man-woman relationships -- California -- Los Angeles -- Drama; Promotions -- California -- Los Angeles -- Drama; Repossession -- California -- Los Angeles -- Drama